Certified OpenStack Administrator study guide - Markelov, Andrey (Apress, 2016)
This guide teaches you how and what to study in order to be best prepared for the Certified OpenStack Administrator exam. This fast-growing technology is creating a market that needs more qualified IT specialists with proven skills. Certified OpenStack Administrator Study Guide covers 100% of the exam requirements for The OpenStack Foundation and will be very helpful for the Mirantis OpenStack Certification Exam. Each theme is taught using practical exercises and instructions for the command line and for the graphical client (Horizon). Each chapter is followed by review questions, complete with answers. Even after you have taken and passed your OpenStack exam, this book will remain a useful reference.